2014
DOI: 10.1042/bj20131677
|View full text |Cite
|
Sign up to set email alerts
|

A Fab fragment directed against the neural cell adhesion molecule L1 enhances functional recovery after injury of the adult mouse spinal cord

Abstract: Lack of permissive mechanisms and abundance of inhibitory molecules in the lesioned central nervous system of adult mammals contribute to the failure of functional recovery, which leads to severe disabilities in motor functions or pain. Previous studies have indicated that the neural cell adhesion molecule L1 constitutes a viable target to promote regeneration. In the present study, we describe the cloning, functional expression in Escherichia coli cells and purification of a recombinant αL1 Fab fragment that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 55 publications
3
10
0
Order By: Relevance
“…Here, we demonstrated that genetic ablation of Mst-1 promotes SCIinduced motor neuron survival. However, although the Hippo/Mst-1 pathway can be stimulated by multiple types of cellular stress, including mechanical stress, DNA damage, and reactive oxygen species , it is still unknown how Mst-1 activation occurs during SCI-induced cellular stress (Hetz et al 2009;Liu et al 2010;Deng et al 2013;Maejima et al 2013;Li et al 2014;Loers et al 2014). Interestingly, consistent with previous report (Lee et al 2013), we found the phosphorylation of Mst-1 at Thr183 was activated in SCI, and the activation was specific for motor neurons.…”
Section: Discussionsupporting
confidence: 89%
“…Here, we demonstrated that genetic ablation of Mst-1 promotes SCIinduced motor neuron survival. However, although the Hippo/Mst-1 pathway can be stimulated by multiple types of cellular stress, including mechanical stress, DNA damage, and reactive oxygen species , it is still unknown how Mst-1 activation occurs during SCI-induced cellular stress (Hetz et al 2009;Liu et al 2010;Deng et al 2013;Maejima et al 2013;Li et al 2014;Loers et al 2014). Interestingly, consistent with previous report (Lee et al 2013), we found the phosphorylation of Mst-1 at Thr183 was activated in SCI, and the activation was specific for motor neurons.…”
Section: Discussionsupporting
confidence: 89%
“…Mean thickness of glial scar was calculated from fixed four areas per section. The scar volume was estimated according to the Cavalieri principle .…”
Section: Methodsmentioning
confidence: 99%
“…The function-triggering, i.e. agonistic action of the Fab fragment of antibody 557 has also been reported [37].…”
Section: Methodsmentioning
confidence: 93%
“…Our previous cell culture experiments with soluble beneficial function triggering monoclonal antibody 557 revealed optimal stimulation of neuronal growth and survival at 50 µg/ml or higher concentrations of 557 antibody in the cell culture medium [37], hence 400 µg/ml was chosen for the in vivo experiments to assure that the maximal stimulatory effect of the antibody can be reached. In these previous experiments we had used 200 µg/ml of a Fab fragment derived from antibody 557 in vivo and shown that the Fab is active in a similar micro-molar range as the IgG.…”
Section: Discussionmentioning
confidence: 99%